An Intertextual Reading of Margaret Atwood’s The Handmaid’s Tale - Šlapkauskaitė, Rūta (Literatūra, 2015)
Since its publication in 1985, Margaret Atwood’s dystopia The Handmaid’s Tale has prominently secured its place among the most widely read novels of Canadian literature. The present article offers a reading of Atwood’s The Handmaid’s Tale as a narrative built on intertextual relationships with other texts, which are directly or implicitly referred to in the novel. This analysis of the novel emphasizes reading as a dynamic semiotic process and employs Gérard Genette’s notion of transtextuality to look into the narrative’s semantic field from the perspective of its paratextual, intertextual and metatextualrelationships. While focusing on the Bible as the major intertext that structures the semantic space of Atwood’s narrative, this intertextual reading of The Handmaid’s Tale also looks at the ways in which the biblical context of Atwood’s novel correlates with the paratexts of Jonathan Swift’s essay A Modest Proposal and sufi philosophy to delineate the dominant strategies of the reading and interpreting of Atwood’s text. Finally, the article analyzes the metatextual level of Atwood’s novel and points out the ways in which the writer ironizes the intertextual nature of her own text and fictionalizes its intertexts, thereby suggesting the impossibility of narrative and interpretative closure.